2024
DOI: 10.15585/mmwr.su7301a3
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Psychosocial Syndemic Conditions and Condomless Anal Intercourse Among Transgender Women — National HIV Behavioral Surveillance Among Transgender Women, Seven Urban Areas, United States, 2019–2020

Rebecca B. Hershow,
Lindsay Trujillo,
Evelyn Olansky
et al.

Abstract: Psychosocial and structural syndemic conditions, including polydrug use and experiencing homelessness, frequently co-occur and might jointly increase HIV risk. Limited studies have assessed racial and ethnic differences in exposure to syndemic conditions and behaviors associated with HIV transmission among transgender women. This report examines the relation between syndemic conditions and condomless anal intercourse (CAI) among transgender women in seven urban areas in the United States to develop HIV prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Findings from the National HIV Behavioral Surveillance indicated that among transgender women, more syndemic conditions were associated with increased condomless anal intercourse across racial and ethnic groups, and the prevalence of different syndemic conditions varied by racial and ethnic group with excess burden among Black and Latina transgender women. [30] Cross-sectional research has also demonstrated the co-occurring and deleterious interactions of syndemic conditions with HIV vulnerability and with adherence to antiretrovirals for HIV prevention and care. [31,32] Alongside risks, it is vital to identify health-promoting factors and resiliencies that may be leveraged for interventions, including gender affirmation, community involvement, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the National HIV Behavioral Surveillance indicated that among transgender women, more syndemic conditions were associated with increased condomless anal intercourse across racial and ethnic groups, and the prevalence of different syndemic conditions varied by racial and ethnic group with excess burden among Black and Latina transgender women. [30] Cross-sectional research has also demonstrated the co-occurring and deleterious interactions of syndemic conditions with HIV vulnerability and with adherence to antiretrovirals for HIV prevention and care. [31,32] Alongside risks, it is vital to identify health-promoting factors and resiliencies that may be leveraged for interventions, including gender affirmation, community involvement, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…5 Repeated experiences of social marginalization and the constant struggle to meet basic needs exact a mental health toll that exacerbates the challenges experienced by transgender women in the United States. Among NHBS-Trans participants, 26% of transgender women had experienced psychological distress during the previous 30 days, 6 and 18% had seriously considered suicide during the previous 12 months. 2 Of transgender women, 22% did not currently have any health care provider with whom they felt comfortable discussing gender identity, and 13% reported having never, at any point in their lives, had a health care provider with whom they had been comfortable discussing their gender identity.…”
mentioning
confidence: 99%